Method for preparing anti-human R47H-TREM2 mutant human monoclonal antibody - ZHOU XIMING (2016)
The invention provides a method for preparing an anti-human R47H-TREM2 mutant human monoclonal antibody. The method comprises the following steps that (1) a polypeptide antigen is synthesized, wherein 201 6-15aa R47H-TREM2 polypeptides are artificially synthesized; antigenic determinants are expanded to both sides with the R47 of TREM2 as the center and around TREM2 gene mutation targets, wherein each polypeptide sequence is staggered by 1-2 aa; and HPLC C-18 reverse column purification and freeze drying are carried out; (2) an R47H-TREM2 mutant polypeptide antigen array (Peptide Array) is prepared; (3) CD22+B-cells are collected; (4) cell culturing is carried out; (5) B-cell immortalization is carried out; and (6) B-cell positive monoclone is screened with the R47H-TREM2 mutant polypeptide antigen array. According to the invention, the human monoclonal antibody is prepared with the B-cell immortalization technology. The human monoclonal antibody has important early clinical diagnosis and therapeutic potentials on Alzheimer's disease (AD) patients.